Antihyperlipidemic Effects of Rhapontin and Rhapontigenin from Rheum undulatum in Rats Fed a High-Cholesterol Diet - Jo, Sung-Pil; Kim, Jeong-Keun; Lim, Young-Hee (Planta Medica, 2014)
Rhapontin was purified from a methanol extract from the roots of Rheum undulatum, and rhapontigenin was produced by an enzymatic transformation of rhapontin. Rats were fed a high-cholesterol diet to induce hyperlipidemia, followed by oral treatment with rhapontin or rhapontigenin (1–5 mg/kg/day). Rhapontin and rhapontigenin treatment resulted in a significant (p < 0.05) dose-dependent decrease in the serum lipid level, while the high-density lipoprotein cholesterol level increased slightly compared with the experimental control. Furthermore, rhapontin and rhapontigenin treatment improved the pathological characteristics of the degenerating fatty liver in high-cholesterol diet-induced hyperlipidemic rats dose-dependently. Aspartate aminotransferase and alanine aminotransferase levels in rhapontin- and rhapontigenin-treated hyperlipidemic rats were not significantly different from those in the control. These results indicate that rhapontin and rhapontigenin can be used as potent antihyperlipidemic agents.
Keywords: Rheum undulatum; Polygonaceae; methoxylated stilbene; antihyperlipidemic effect; high-cholesterol diet